Serial Cardiovascular Magnetic Resonance Studies Prior to and After mRNA-Based COVID-19 Booster Vaccination to Assess Booster-Associated Cardiac Effects - Meier, Claudia; Korthals, Dennis; Bietenbeck, Michael; Chamling, Bishwas; Drakos, Stefanos; Vehof, Volker; Stalling, Philipp; Yilmaz, Ali (Frontiers in Cardiovascular Medicine, 2022)
Background mRNA-based COVID-19 vaccination is associated with rare but sometimes serious cases of acute peri-/myocarditis. It is still not well known whether a 3rd booster-vaccination is also associated with functional and/or structural changes regarding cardiac status. The aim of this study was to assess the possible occurrence of peri-/myocarditis in healthy volunteers and to analyze subclinical changes in functional and/or structural cardiac parameters following a mRNA-based booster-vaccination. Methods and Results Healthy volunteers aged 18–50 years (n = 41; m = 23, f = 18) were enrolled for a CMR-based serial screening before and after 3rd booster-vaccination at a single center in Germany. Each study visit comprised a multi-parametric CMR scan, blood analyses with cardiac markers, markers of inflammation and SARS-CoV-2-IgG antibody titers, resting ECGs and a questionnaire regarding clinical symptoms. CMR examinations were performed before (median 3 days) and after (median 6 days) 3rd booster-vaccination. There was no significant change in cardiac parameters, CRP or D-dimer after vaccination, but a significant rise in the SARS-CoV-2-IgG titer (p < 0.001), with a significantly higher increase in females compared to males (p = 0.044). No changes regarding CMR parameters including global native T1- and T2-mapping values of the myocardium were observed. A single case of a vaccination-associated mild pericardial inflammation was detected by T2-weighted CMR images. Conclusion There were no functional or structural changes in the myocardium after booster-vaccination in our cohort of 41 healthy subjects. However, subclinical pericarditis was observed in one case and could only be depicted by multiparametric CMR.